La riforma delle valutazioni di efficacia della spesa per investimenti pubblici: l’avvio di una nuova stagione? - Rubino, Piero (Argomenti, 2016)
Public investments have been hit hard worldwide by the budgetary constraints aimed at mitigating the impact of the financial crisis. Recent studies carried out by prominent research institutions have shown the adverse effects on output growth of a shortfall in public infrastructure. To commit resources to public infrastructure is essential to select public projects capable of delivering quality and cost-effective services as to increase total productivity path. A crucial step is to engage in feasibility assessments prior to expenditure decisions. The recent overhauling of the appraisal for public investment enacted in Italy is consistent with this goal. The paper briefly discusses strengths and weaknesses of the new framework.